The Role of Digital Transformation in Promoting Economic Growth in Iraq 2010-2022 - Fatimah Faraj Saad (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Economic growth is one of the most important goals countries seek to achieve.Now, when the world is witnessing a revolution in information and communicationtechnology, economic growth has become entirely linked to the state's readiness fordigital transformation and its degree of reliance on advanced means. The researchproblem of the present study revolves around the fact that Iraq is one of the countrieslagging behind in terms of the use of modern technology due to the extraordinaryconditions, which impacted various areas of life, especially the field of informationand communication technology, leading to the weak application of the digitaltransformation process. The present study aims to explore the challenges facingdigital transformation in Iraq and determine the extent of hindering economic growth.The SPSS is employed to reveal the correlation between digital transformationindicators and economic growth in Iraq 2010-2022 . The results of the present studyindicate that there is a slowdown in digital transformation in Iraq due to lack ofinfrastructure and reliance on foreign markets in providing information andcommunication technology resources as a result of not manufacturing them locally .One of the important recommendations of the present study is to spread technical anddigital awareness by providing training programs in order to prepare qualified andtrained human staff that contribute to the management of the digital transformationprocess.